Research from Low-Income and Middle-Income Countries will Benefit Global Health and the Physiotherapy Profession, but it Requires Support - Saurab Sharma; Arianne Verhagen; Mark Elkins; Jean-Michel Brismée; George D. Fulk; Jakub Taradaj; Lois Steen; Alan Jette; Ann Moore; Aimee Stewart; Barbara J. Hoogenboom; Anne Söderlund; et al. (International Journal of Sports Physical Therapy)
Disparities in research publications are common in the physiotherapy and rehabilitation fields.^1^ A small proportion of published research arises from low-income and middle-income countries (LMICs),^1,2^ home to 85% of the world’s population. Systems-level, institutional-level, and individual-level factors contribute to these disparities. With urgent and unified actions, global health and the standard of physiotherapy research in LMICs can be improved and strengthened. In this editorial, we will discuss the challenges encountered by researchers from LMICs in conducting and publishing high-quality research and propose potential strategies to address these challenges.